COMING OUT OF THE GHOSTLY GAY CHILDREN IN TRUMAN CAPOTE’S «OTHER VOICES, OTHER ROOMS» AND HARPER LEE’S «TO KILL A MOCKINGBIRD» - Świetlicki, Mateusz (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The author of the proposed article traces and analyzes literary representation of queer children (using Kathryn Bond Stockton’s terminology) in two American novels: Truman Capote’s Other Voices, Other Rooms (1948) and Harper Lee’s To Kill A Mockingbird (1960). He claims that queer children have long been a part of American literature. Capote’s Joel Knox and Idabel Thompkins just like Lee’s Dill Harris and Scout Finch appear as “protogay” and different to other “normative” children in the novels, such as Idabel’s sister and Scout’s brother, who represent how a “real” Southern girl and boy should dress and behave like. The authors show that re-reading and re-interpreting To Kill a Mockingbird and Other Voices, Other Rooms helps queer theory to allow the “closeted” queer children to finally come out of their closets.